Uric Acid and P-Wave Dispersion in Subjects with Heart Failure - Recep Kurt; Anıl Şahin (Medical Laboratory Technology Journal, 2021)
Uric acid used as a marker of cardiovascular risk, which is associated with oxidative stress and inflammation. P-wave dispersion (PWD) is an electrocardiographic measure, which shows heterogeneity of atrial depolarization. It has demonstrated that there is an association of increased PWD with atrial fibrillation. This article aimed to investigate the relationship between PWD and uric acid in subjects with heart failure (HF). This descriptive method, cross-sectional study included a total of 315 stable HF outpatients. The subjects were classified into two groups by their PWD: the normal PWD group consisted of subjects with a PWD lower than 40 ms (n = 201), and the increased PWD group consisted of subjects with a PWD higher than or equal to 40 ms (n = 114). Significantly, the results showed higher uric acid levels determined in the increased PWD group, in comparison with the normal PWD group (7.4 ± 1.6 mg/dL, vs. 6.5 ± 1.6 mg/dL p < 0.001). Univariate analyses revealed an association between uric acid, blood urea nitrogen, systolic pulmonary artery pressure, left atrial diameter, and increased PWD. In multivariate logistic regression analysis, there was an association of uric acid level (OR: 1.293; 95% CI: 1.106-1.511, p: 0.001), systolic pulmonary artery pressure (OR: 1.027; 95% CI: 1.011-1.044, p: 0.001), and left atrial diameter (OR: 1.754; 95% CI: 1.028-2.992, p: 0.039) with PWD. The receiver operating characteristics (ROC) curve analysis demonstrated that the optimal cut-off level of uric acid for predicting increased PWD was ≥ 7.1 mg/dL with a specificity of 77 percent and a sensitivity of 81 percent. Conclusion of our study results suggested that serum uric acid levels independently correlated with PWD in subjects with HF.